Biotechnological Application in the Development of a Standardized Phytotherapeutic Product of Barbatimão for the Treatment of Acne (CIPEEX, 2025)
INTRODUCTION: Barbatimão (Stryphnodendron adstringens), a native species of the Brazilian Cerrado, is widely recognized in traditional medicine for its wound-healing, antimicrobial, and anti-inflammatory properties, primarily attributed to condensed tannins, flavonoids, and phenolic acids. Recent studies validate its application in skin disorders, reinforcing its potential in the development of dermatological phytomedicines. Acne stands out as one of the most prevalent dermatological conditions with significant psychosocial impact, whose current treatments are often limited by adverse effects and microbial resistance. In this context, combining the traditional use of barbatimão with advanced pharmaceutical technologies, such as nanoencapsulation, emerges as a promising strategy to enhance its efficacy by ensuring greater stability, improved skin permeability, and controlled release of active compounds.OBJECTIVE: To propose the theoretical development of a nanoencapsulated phytotherapeutic gel based on standardized S. adstringens extract for acne treatment, integrating scientific evidence and pharmaceutical innovation.METHODS: The protocol includes: (i) a scientific review of the pharmacology and safety of barbatimão; (ii) extraction of active metabolites using cost-effective solvents to maximize yield and purity; (iii) nanoencapsulation of barbatimão extract in an aqueous gel to optimize stability and bioavailability; (iv) chemical and physicochemical standardization, including tannin quantification, chromatographic profiling by HPLC, and microbiological and stability testing; and (v) regulatory analysis in line with national phytotherapeutic requirements, while also considering sustainability and Cerrado biodiversity conservation.EXPECTED RESULTS: The nanoencapsulated barbatimão gel is expected to demonstrate significant pharmaceutical and clinical benefits, including enhanced skin permeability and controlled release of tannins; improved chemical and physical stability of the extract; antimicrobial activity against Staphylococcus aureus, a pathogen associated with acne; anti-inflammatory effects through cytokine modulation and edema reduction; and wound-healing properties with accelerated tissue contraction and reorganization. Additionally, the proposed formulation is expected to be commercially viable by combining efficacy, technological innovation, and sustainability, thereby supporting its integration into both public and private healthcare systems.CONCLUSIONS: The development of a nanoencapsulated barbatimão phytotherapeutic gel represents a strategic opportunity in the pharmaceutical field. The proposal bridges traditional knowledge, scientific evidence, and biotechnology, resulting in a product with superior efficacy potential, enhanced safety, and sustainable production. At the same time, it promotes the valorization of Cerrado biodiversity and associated traditional knowledge, reinforcing Brazil’s leadership in research and innovation in phytotherapeutic medicines.
Keywords: Stryphnodendron adstringens; Herbal medicines; Condensed tannins; Nanotechnology; Biotechnology; Brazilian Pharmacopoeia